2017
DOI: 10.3171/2016.10.focus16368
|View full text |Cite
|
Sign up to set email alerts
|

Pathological characteristics of spine metastases treated with high-dose single-fraction stereotactic radiosurgery

Abstract: OBJECTIVE Spine radiosurgery is increasingly being used to treat spinal metastases. As patients are living longer because of the increasing efficacy of systemic agents, appropriate follow-up and posttreatment management for these patients is critical. Tumor progression after spine radiosurgery is rare; however, vertebral compression fractures are recognized as a more common posttreatment effect. The use of radiographic imaging alone posttreatment may makeit difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The hypothesis that ablative dosing leads to improved tumor control is not new. The application of higher biological doses was preferred for radioresistant tumors, those previously irradiated, and oligometastatic disease [9,16,25]. Experiences with singlefraction SBRT (24 Gy) is limited to a few datasets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis that ablative dosing leads to improved tumor control is not new. The application of higher biological doses was preferred for radioresistant tumors, those previously irradiated, and oligometastatic disease [9,16,25]. Experiences with singlefraction SBRT (24 Gy) is limited to a few datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one third of cancer patients will develop bone metastases, approximately two thirds of which involve the vertebral column, most commonly at the thoracic and lumbar levels [1,2]. Conventionally fractionated 3D-conformal radiotherapy (3DCRT) is a well-recognized palliative treatment for painful bone metastases [3][4][5][6][7][8][9][10][11][12][13][14]. Comprehensive meta-analyses by Sze et al and Wu et al have provided consistent data regarding pain response after conventional external beam radiotherapy [13,14].…”
mentioning
confidence: 99%
“…Reliance on SRS to provide local tumor control has allowed surgeons to decrease the extent of surgical intervention, thereby minimizing the risk of complications and systemic therapy interruption. Spinal SRS has been shown to be a tumor ablative treatment 18 and provide durable and consistent tumor control, with reports of histology-independent 98% local control at 4-year follow-up. 19 Separation surgery followed by SRS has been previously shown to be an effective treatment strategy providing a greater than 95% control rate, for previously considered radioresistant tumors in a retrospective review of 186 cases.…”
Section: Discussionmentioning
confidence: 77%
“…In order to accurately characterise imaging findings as being in keeping with tumour response, tumour progression, pseudoprogression, and VCF either secondary to tumour or treatment, radio‐pathologic studies are needed. MSKCC reported in 2017 on 30 patients (out of a cohort of 582 who underwent single‐fraction spine SRT) who underwent surgical instrumentation for either VCF, instability or tumour progression 46 . Overall, they found that active tumour was present in only 22% of specimens (60% of surgical intervention cases and 5% of vertebral augmentation cases).…”
Section: Resultsmentioning
confidence: 99%